METHODOLOGY AND METHODS OF SCIENTIFIC RESEARCH IN PEDAGOGY - Mahammatova Ma'muraxon; Erkinjonova Niginabonu (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article systematically analyzes the modern scientific research methodology of pedagogical science and its specific research methods. During the research, the role of methodological principles in the objective study of educational processes, identification of existing problems and finding scientifically based solutions to them is highlighted. Also, the importance of theoretical and empirical research methods (observation, interview, pedagogical experiment, test, etc.) in understanding pedagogical reality is revealed.